Rachunek kosztów jakości i możliwości jego zastosowania w zakładach opieki zdrowotnej - Kludacz, Magdalena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The changes in the financing system of health care and the growing competition between medical establishments oblige their managers to look for the new tools of cost management. One of the main tools of cost management is the quality cost account which is an instrument of quality improvement and efficiency management. This article describes principal issues in cost accounting, which is connected with the assurance quality and failure quality of medical services. It presents the reasons for the development, the structure, principles and factors determining the application of the quality cost account to the medical establishments. Information regarding their quality costs becomes the basis for making strategic decisions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 162-171